Migration challenges of legacy software to the cloud: a socio-technical perspective - Bashair Althani (Cogent Business & Management)
Cloud computing offers significant benefits for organizations, yet migrating legacy software to the cloud presents unique challenges for higher education institutions. This study investigates these challenges from a socio-technical perspective, addressing gaps in existing research. Using a mixed-method approach, we surveyed and interviewed stakeholders across five Saudi Arabian universities. Our findings reveal a complex interplay between technical, social, and organizational factors influencing cloud migration decisions. While institutions recognize benefits like improved accessibility and cost-effectiveness, they face barriers including technical complexities, resource constraints, and organizational resistance. The study’s key contribution is an integrated model for legacy software migration in higher education, emphasizing a resource-centric approach, pre-migration readiness, and agile decision-making tools. This model provides a comprehensive framework for policymakers and institutional leaders, bridging technical requirements with organizational realities to facilitate effective cloud adoption strategies in higher education.